Public Policy Advocacy Process on the Protection of Indonesian Migrant Workers conducted by Institute for Education Development, Social, Religious, and Cultural Studies (INFEST) - Laras Ningrum Fatmasiwi (IJISH (International Journal of Islamic Studies and Humanities), 2019)
This article describes the working patterns of local NGO networks for the advocacy of Indonesian Migrant Workers/Pekerja Migran Indonesia (PMI). INFEST (Institute for Education Development, Social, Religious, and Cultural Studies) together with Network of Migrant Workers/Jejaring Buruh Migran (JBM) collaborated to develop a proposed bill in order to amend the article on Protection of Indonesian Migrant Workers. Nowadays, a lot of cases regarding to protection of migrant workers has not been fullfiled due to less attention of Indonesian government to provide a proper law on the protection of migrant workers. The author uses the nine-step advocacy approach described by Roem Tomatimasang, which forms the core circle, selects strategic issues, designs goals and strategies, processes data and packs information, mobilizes allies and advocates, submits counter draft, influences policy makers, shapes public opinion, and build a base of movement. Through these stages, INFEST and JBM conduct advocay to change the regulation of protection of PMI.